Optimalisasi Publikasi Guru di Era Merdeka Belajar: Kolaborasi MGMP dan Perguruan Tinggi dalam Penguatan Kompetensi Penulisan Ilmiah - Nugroho, Lucky; Oktris, Lin; Apollo, Apollo; Andesto, Ronny; Soeharjoto, Soeharjoto; Putra, Yananto Mihadi; Purnama, Adhy (Dedikasi : Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem of low teacher skills in writing scientific articles is a challenge in developing professionalism and fulfilling publication obligations for promotion. This Community Service Program aims to improve the ability of MGMP Accounting Central Jakarta 1 teachers in compiling scientific articles based on Classroom Action Research through structured training and intensive mentoring. The activity was carried out with a participatory approach through workshops, hands-on practice, and continuous online and hybrid consultations. The activity results showed a significant increase in participants' understanding of scientific writing techniques, with 80% of participants drafting articles and 30% ready to be submitted to accredited journals. Key recommendations include follow-up mentoring to the publication stage and establishing a teacher writers' forum to encourage collaboration and sustainability capacity building.